Justification by the Faithfulness of Jesus Christ - Harrington, Chad (The Asbury journal, 2010)
This essay focuses on Paul's description of justification by faith in Galatians 2:16. Scholars such as J.D.G. Dunn and N.T. Wright have recently challenged more traditional perspectives on justification. This essay appropriates some of these challenges to Paul's letter to the Galatians. The problem for Paul is that some Christians are distorting the gospel (Gall:7) and excluding Gentiles Christians (2:12-13). Paul's solution is gospel reorientation. Instead of being a Torah-focused church, he instructs the Galatian church to be Christ-centered. This essay examines justification, works of law, and faith/fulness to reveal Paul's rhetorical purposes by analyzing socio-rhetorical backgrounds and literary, grammatical, and theological issues. The thesis is that Paul's rhetoric in Galatians 2:16 is sociological, moving the church to unity. Pauline justification is not only forensic language but also ecclesial language. Paul's usage of works of law was not only about theology but also about church unity. His reference to the faith of Christ is not a description of how one receives final salvation but of how God justifies his people, through the faithfulness of Jesus Christ. The implications of this thesis may have dramatic implications for Pauline studies and even contemporary church life.